Symposium 7: Ritual performances and collective intelligence: Theoretical frameworks for analysing emerging activity patterns in Cloudworks - Alevizou, Panagiota; Conole, Gráinne; Culver, Juliette; Galley, Rebecca (Proceedings of the International Conference on Networked Learning, 2010)
This paper provides an overview of emerging activity patterns on Cloudworks, a specialised site for sharing and debating ideas as well as resources on teaching, learning and scholarship in education. It provides an overview of activities such as ‘flash debates’, ‘blended workshops’ and ‘open reviews’ and seeks to situate dialogic interchanges and structures of involvement within the following theoretical frameworks: a) Goffman’s notions of ‘face-work’ and ‘ritual performance’; and b) and secondly, notions of collective intelligence. The paper argues that these perspectives can offer a unique contribution to the study and analysis of sociality (Bouman et al, 2007) bounded in the context of technologically mediated networked learning, with wider implications for understanding matters of participation, self-representation, reflection and expansion in education.